2020
DOI: 10.1038/s41598-020-75127-0
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in broadband power and alpha peak frequency observed during long-term isolation

Abstract: Prolonged periods of social isolation and spatial confinement do not only represent an issue that needs to be faced by a few astronauts during space missions, but can affect all of us as recently shown during pandemic situations. The fundamental question, how the brain adapts to periods of sensory deprivation and re-adapts to normality, has only received little attention. Here, we use eyes closed and eyes open resting-state electroencephalographic (EEG) recordings to investigate how neural activity is altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…The aim of the present work was to assess if 1/ƒ aperiodic neural dynamics predict visuomotor performance. Aperiodic resting-state EEG activity is thought to be behaviourally relevant in predicting cognitive capacity (Cross et al, 2020;Ouyang et al, 2020) with higher 1/ƒ intercept reflecting higher neural population spiking (Manning et al, 2009;Miller et al, 2012) and steeper 1/ƒ slope reflecting a greater excitation-inhibition balance (Lendner et al, 2020;Weber et al, 2020). Despite the apparent association between 1/ƒ aperiodic parameters and information processing capacity, to date, there has been no empirical test of these parameters as individual predictors of visuomotor performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of the present work was to assess if 1/ƒ aperiodic neural dynamics predict visuomotor performance. Aperiodic resting-state EEG activity is thought to be behaviourally relevant in predicting cognitive capacity (Cross et al, 2020;Ouyang et al, 2020) with higher 1/ƒ intercept reflecting higher neural population spiking (Manning et al, 2009;Miller et al, 2012) and steeper 1/ƒ slope reflecting a greater excitation-inhibition balance (Lendner et al, 2020;Weber et al, 2020). Despite the apparent association between 1/ƒ aperiodic parameters and information processing capacity, to date, there has been no empirical test of these parameters as individual predictors of visuomotor performance.…”
Section: Discussionmentioning
confidence: 99%
“…The power-law exponent, or β, reflects the steepness of the 1/ƒ slope, with higher β values indicating a steeper slope and lower values reflecting a shallower (i.e., flatter) slope (He, 2014). Mechanistically, the 1/ƒ slope is argued to reflect an excitation-inhibition balance in recurrent neural networks which maximises information processing capacities (Lendner et al, 2020;Weber et al, 2020), with steeper slopes indexing enhanced neural inhibition and vice versa. Aperiodic activity can also be quantified by its spectral offset (i.e., the intercept), with a higher intercept hypothesized to be reflective of increased neural population spiking (Manning et al, 2009;Miller et al, 2012), and is positively correlated with the blood-oxygen-level-dependent (BOLD) signal (Winawer et al, 2013;Jacob et al, 2021) obtained from functional magnetic resonance imaging (fMRI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent interventional rs-EEG study in healthy humans showed that ketamine and anesthesia administration, which respectively tip the balance in favor of cortical excitation (increase in EIB) and inhibition (decrease in EIB), resulted in the expected decrease and increase in 1/f slope (33). Since then, several recent studies have shown the reliability of this measure using human scalp EEG activity in both healthy (29)(30)(31) and clinical populations (6,29,34).…”
Section: Introductionmentioning
confidence: 99%
“…Neurophysiological brain signal consists of periodic oscillatory activity and aperiodic activity (1/f slope) of the non-oscillatory PSD background (27), which have been shown to play functionally distinct roles (28). While more conventional approaches have focused on narrowband oscillations or frequency band ratios, there has been a current upsurge in neuroscience research in the past year focusing on 1/f slope as a unique neurophysiological marker (6,(28)(29)(30)(31). Simulation data with local field potentials demonstrate that 1/f slope inversely reflects EIB (32), a finding that has been validated in in vivo animal models in which anesthesia administration led to an increase in 1/f slope or steepening of the PSD decay (32).…”
Section: Introductionmentioning
confidence: 99%